Expression of heparanase in basal cell carcinoma and squamous cell carcinoma - Maria Aparecida Silva Pinhal; Maria Carolina Leal Almeida; Alessandra Scorse Costa; Thérèse Rachell Theodoro; Rodrigo Lorenzetti Serrano; Carlos D'Apparecida Santos Machado Filho (Anais Brasileiros de Dermatologia, 2016)
Abstract: Background: Heparanase is an enzyme that cleaves heparan sulfate chains. Oligosaccharides generated by heparanase induce tumor progression. Basal cell carcinoma and squamous cell carcinoma comprise types of nonmelanoma skin cancer. Objectives: Evaluate the glycosaminoglycans profile and expression of heparanase in two human cell lines established in culture, immortalized skin keratinocyte (HaCaT) and squamous cell carcinoma (A431) and also investigate the expression of heparanase in basal cell carcinoma, squamous cell carcinoma and eyelid skin of individuals not affected by the disease (control). Methods: Glycosaminoglycans were quantified by electrophoresis and indirect ELISA method. The heparanase expression was analyzed by quantitative RT-PCR (qRTPCR). Results: The A431 strain showed significant increase in the sulfated glycosaminoglycans, increased heparanase expression and decreased hyaluronic acid, comparing to the HaCaT lineage. The mRNA expression of heparanase was significantly higher in Basal cell carcinoma and squamous cell carcinoma compared with control skin samples. It was also observed increased heparanase expression in squamous cell carcinoma compared to the Basal cell carcinoma. Conclusion: The glycosaminoglycans profile, as well as heparanase expression are different between HaCaT and A431 cell lines. The increased expression of heparanase in Basal cell carcinoma and squamous cell carcinoma suggests that this enzyme could be a marker for the diagnosis of such types of non-melanoma cancers, and may be useful as a target molecule for future alternative treatment.